Efficient immobilization of Cd2+ by nanoscale carbonate hydroxyapatite synthesized by ureolytic bacteria. (10th January 2021) - Xing, Yonghui; Liu, Song; Luo, Xuesong; Wan, Wenjie; Wan, Jie; Zhang, Tianyuan; Chen, Wenli; Huang, Qiaoyun
Abstract: As one of the five most toxic heavy metals, cadmium pollution seriously endangers human health and food safety. Carbonate hydroxyapatite has attracted our attention because of its excellent cleaning ability. However, few ecofriendly synthetic processes of nanoscale carbonate hydroxyapatite limit its application. In this study, we designed a medium that was used to prepare carbonate hydroxyapatite through microbial mineralization. The nano-flaky structure gives it a large specific surface area, which not only can achieve rapid adsorption of Cd 2+ but also has a large adsorption capacity (270 mg/g). Dynamic adsorption experiments showed that adsorption is a spontaneous endothermic process. Ion exchange, surface complexation, and co-precipitation are the main adsorption mechanisms. This simple and readily available bio-carbonate hydroxyapatite provides potential candidates for heavy metal bioremediation in polluted environments. Graphical abstract: Image 1 Highlights: A new method for synthesizing CHAP is proposed. Cd 2+ adsorption capacity of BCHAP is related to its nano-flaky structure. BCHAP-immobilization of Cd 2+ is mainly a spontaneous ion exchange process. Our findings highlight the impact of biomineralization on the circulation of heavy metals.